2004
DOI: 10.5194/acp-4-391-2004
|View full text |Cite
|
Sign up to set email alerts
|

Urban aerosol number size distributions

Abstract: Abstract. Aerosol number size distributions have been measured since 5 May 1997 in Helsinki, Finland. The presented aerosol data represents size distributions within the particle diameter size range 8-400 nm during the period from May 1997 to March 2003. The daily, monthly and annual patterns of the aerosol particle number concentrations were investigated. The temporal variation of the particle number concentration showed close correlations with traffic activities. The highest total number concentrations were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
127
4
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 260 publications
(161 citation statements)
references
References 54 publications
(56 reference statements)
28
127
4
2
Order By: Relevance
“…The average nighttime background concentrations, calculated using short-time measurements, were ∼6000 #/cm 3 and 10 000 #/cm 3 for summer and winter, respectively. Hussein et al (2004) reported rather similar nighttime background concentration values of 8000 #/cm 3 and 10 000 #/cm 3 during the summer and winter seasons, respectively. The average daytime background concentrations are shown by the dashed lines in Fig.…”
Section: Correlation Of Particle Emissions and Traffic Ratementioning
confidence: 52%
See 4 more Smart Citations
“…The average nighttime background concentrations, calculated using short-time measurements, were ∼6000 #/cm 3 and 10 000 #/cm 3 for summer and winter, respectively. Hussein et al (2004) reported rather similar nighttime background concentration values of 8000 #/cm 3 and 10 000 #/cm 3 during the summer and winter seasons, respectively. The average daytime background concentrations are shown by the dashed lines in Fig.…”
Section: Correlation Of Particle Emissions and Traffic Ratementioning
confidence: 52%
“…2a. Hussein et al (2004) reported maximum morning rush hour concentrations of approximately 25 000 #/cm 3 and 17 500 #/cm 3 , during the summer and winter seasons, correspondingly. As expected, the roadside concentrations during the morning rush hours at Itäväylä were much higher, averaging approximately 100 000 #/cm 3 in the winter and 50 000 #/cm 3 in the summer.…”
Section: Correlation Of Particle Emissions and Traffic Ratementioning
confidence: 99%
See 3 more Smart Citations